Persepsi diri, Ideal diri, Sikap dan Perilaku K-Drama Lovers - Desi, Desi; Bezaleel, Michael; Noky, Rhevy Griselia (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
The existence of Korean Drama which has been in Indonesia for 20 years has had its own impact on the development of individuals who enjoy it, especially among teenagers. Easy access, diverse storylines, and interesting visual treats for the cast and location settings make Korean Dramas always awaited by K-Drama Lovers. In teenagers, watching Korean Dramas intensely can affect the way they view themselves, determine their ideals, attitudes and behaviors, which can be positive, or vice versa, negative. The purpose of this study is to describe self-perception, self-ideal and attitudes and behavior of teenagers who like Korean Dramas. Methods: The research in this study was qualitative with the number of participants as many as 10 teenagers, with data collection time in March-April 2021. Results: Self-perception, self-ideal, attitudes and behavior of participants were influenced by genre, culture and characters in Korean Drama. Conclusion: Adolescents perceive themselves as individuals who love and respect themselves as well as